Molecular mechanisms of determination in Drosophila. - Bienz, M. (Current Opinion in Cell Biology, 1992)
A number of Drosophila proteins have been identified that play key roles in the establishment of active or inactive states of selector gene expression. Interactions between these proteins and their target selector genes are beginning to be understood, shaping our molecular view as to how stable determination of cells is achieved.